ISOLATION AND IDENTIFICATION OF AZOTOBACTER OF SOME TYPE OF LAND USE IN JEGU VILLAGES - Ni Nengah Soniari; I Wayan Dana Atmaja (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2019)
Conventional farming systems have a negative impact on the life of Azotobacter. Through the results of this study, we want to provide information on the existence of Azotobacter in several rhizosphere of cultivated plants, and looking for isolates that have advantages as biofertilizers and decomposers. This research is an exploration of bacteria Azotobacter spp. from several plant rhizosphere namely: organic and inorganic rice paddy, cassava, coconut, and chocolate. Three samples was taken from each type of land use, so that the number of isolate sources were 15 samples. All analyzes were conducted at Soil Biology Laboratory, Faculty of Agriculture Udayana University. This study aims to find isolates of Azotobacter spp. which is superior to be utilized as biofertilizer and decomposer. Parameters used to support isolation and identification results are total population of bacteria Azotobacter spp., soil respiration, gram staining, halo zone and optical density. The results showed that organic rice rhizosphere was the best isolate source compared with inorganic rice rhizosphere, coconut, cassava and chocolate. Isolate from this organic rice rhizosphere has the highest total population (40.10 cfu x107g-1 soil), on positive catalase test yield bubbles and optical density (average 1.217ABS at 550 nm wavelength). While the superior isolates of Azotobacter spp. As biofertilizer and decomposer candidates are TSO2 isolates (samples from organic rice plant rhizosphere) with soil respiration rate (8.057mgC-CO2 kg-1 soil/day), high optical density (1.147 ABS on spectrophotometer with 550 nm wavelength) and highest halo zone diameter (10 mm).